ONLINE SPEAKING TEST APPLICATION: IS IT EFFECTIVE IN ELEVATING STUDENTS’ ENGLISH SELF-EFFICACY, ANXIETY AND MOTIVATION? - Putu Ayu Asty Senja Pratiwi; Ni Luh Nyoman Seri Malini (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study aims to evaluate the impact and efficacy of the Online Speaking Test (OST) application on students' motivation and self-efficacy to optimize English learning and produce students with greater English language proficiency. Using a variety of techniques, such as pre-test, observation, interviews, treatment in using the OST, and post-tests to see whether changes had occurred before and after the treatment, 102 university students from various faculties in Bali’s university participated in this study. Employing the OST, the research revealed variations between the factors of rising and decreasing student motivation, anxiety, and self-confidence following treatment and post-treatment. Nevertheless, there was a very small variation in the proportion of students whose self-confidence improved following therapy, which was brought on by variations in the students' English proficiency levels. The students with excellent proficiency inboth comprehending and using English did not encounter major challenges when using the online speaking test. Students who feel less confident, on the other hand, have a different experience. Due to differences in prior learning experience, learner characteristics, teaching and learning methods, learners’ motivations and the urgency of language acquisition, an OST may results differently according several factors affecting the learners intrinsically and extrinsically.